Education and Socialization Of Pre Screening Developmental Questionnaire For Early Detection Of Child Development - Herawati, Yanti; Herlina, Lina; Arini, Wike (CV Media Inti Teknologi, 2024)
A preliminary research at PMB Bidan Wike A in June 2023 revealed the developmental outcomes of toddlers using the Pre-Screening Development Questionnaire (KPSP). Out of 189 toddlers, 77.8% exhibited typical development, 21% had questionable development, and 1.2% displayed developmental deviations. Many mothers lacked knowledge about the care and examination procedures related to the pre-screening developmental questionnaire. This community service aims to provide mothers with knowledge about child growth and development while introducing the Pre-Screening Development Questionnaire instrument. This community service utilizes counseling and socialization methods for mothers with toddlers. Participants will undergo both pretest and posttest assessments. This initiative employs the Developmental Pre-Screening Questionnaire instrument and self-evaluation notes. In the initial stage, the counselor will engage in a question-and-answer session, followed by assessing the mother's comprehension using the feedback method. Subsequently, it proceeds with discussions or brainstorming sessions. The outcomes of the community service revealed that following counseling and the socialization of KPSP to mothers of toddlers, their knowledge increased by 93%. Early and regular screening is of utmost importance to prevent developmental deviations in toddlers, allowing for prompt treatment of any deviations that may arise. Growth screening enables the assessment of children's nutritional status, while developmental screening for children under five can be conducted using the KPSP (Developmental Pre-Screening Questionnaire) method. Keywords: growth screening, nutritional status, developmental screening, KPSP method.